2021
DOI: 10.1136/bmjopen-2021-049045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic conditions and multimorbidity in Estonia: a population-based cross-sectional study

Abstract: ObjectivesPrevalence estimates for specific chronic conditions and multimorbidity (MM) in eastern Europe are scarce. This national study estimates the prevalence of MM by age group and sex in Estonia.DesignA population-based cross-sectional study, using administrative data.SettingData were collected on 55 chronic conditions from the Estonian Health Insurance Fund from 2015 to 2017. MM was defined as the coexistence of two or more conditions.ParticipantsThe Estonian Health Insurance Fund includes data for appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 35 publications
2
14
0
1
Order By: Relevance
“…Our findings are in agreement with the known paradox and other studies that multimorbidity increases with age, as long-term diseases accumulate with age. 10 25 It is interesting to note that in our study population, older age only explained part of the augmented risk of multimorbidity. We identified that other factors (sex, education level and employment status) are responsible for a substantial part of the association with multimorbidity.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our findings are in agreement with the known paradox and other studies that multimorbidity increases with age, as long-term diseases accumulate with age. 10 25 It is interesting to note that in our study population, older age only explained part of the augmented risk of multimorbidity. We identified that other factors (sex, education level and employment status) are responsible for a substantial part of the association with multimorbidity.…”
Section: Discussionmentioning
confidence: 70%
“…Consequently, it has not been possible to evaluate and develop patient-centred prevention and treatment strategies targeting multimorbidity and such risk factors. The COVID-19 pandemic further drew attention to the crucial contribution of multimorbidity to the need for sound public health measures and rapid identification of effective medical interventions grounded on risk stratification 10. To better manage the consequences of such an adverse phenomenon, a better understanding of the prevalence and factors associated with multimorbidity among diverse study populations became essential.…”
Section: Introductionmentioning
confidence: 99%
“… 154 Brazil UMIC 2020 2015 Cross-sectional The ISA-Capital health survey Self-reported and Objective 1019 ≥60 67.7 40.3 10 40 Jürisson et al. 155 Estonia HIC 2021 2015–2017 Cross-sectional Estonian Health Insurance Fund Objective 909,477 ≥25 53.4 45.9 55 39.8 a Ascertainment of morbidities- Objective: medical records/clinical examinations. …”
Section: Resultsmentioning
confidence: 99%
“…Study subjects were assigned a unique identifier decoupled from personal identification information to enable longitudinal tracking of care while maintaining patient privacy. The same database and methodology were used when analyzing MM prevalence in Estonia [ 13 ].…”
Section: Methodsmentioning
confidence: 99%